Cutaneous myeloid sarcoma associated with chronic myeloid leukemia - Erica Rodrigues de Araujo Vasconcelos; Alexander Richard Bauk; Mayra Carrijo Rochael (Sociedade Brasileira de Dermatologia, 2017)
Abstract: Myeloid sarcoma is an extramedullary tumor of malignant myeloid cells often associated with acute myeloid leukemia, chronic myeloproliferative disorders and myelodysplastic syndromes. The skin is one of the most commonly affected sites. We report a rare case of cutaneous myeloid sarcoma associated with chronic myeloid leukemia.